Peel's Bibliography of the Canadian Prairies to 1953 - Ingles, Ernie, 1948-2020 (Book collections on Project MUSE., 2003)
"The previous edition of Bruce Peel's Bibliography was hailed by authorities as the single, finest introduction to the literature of the Canadian Prairies ever compiled, and one of the pioneering monuments of Canadian bibliographic scholarship. Although he had planned to issue only a supplement to the second edition, additional entries multiplied until it became clear that an entirely new edition was warranted. Sixty-five per cent larger than its predecessor, this edition features over 3000 new entries, bringing the total to more than 7400. All entries are integrated into one continuously numbered sequence, and a table has been added that cross references the entry numbers to those of the second edition. As well, the annotations, biographical notes, author, title, and subject indexes have been revised and expanded." "Ingles and Distad's new edition will prove even more invaluable to students and academics interested in the history of the Prairie provinces, Prairie writers, or even the pattern of migration within Canada itself."--Jacket